Perceptions of Social Capital Before and After the Perpetration of Femicide, Homicide, and Other Serious Crimes: Evidence from Argentina - FarrHenderson, Maya (Journal of interpersonal violence, 2025)
Over the past two decades, femicide—the gender-based killing of women or girls—has become an issue of international concern. Yet relatively little data on perpetrators exist. Current research primarily focuses on individual risk factors with less attention on community and societal factors. We use a social capital approach to examine femicide by analyzing the extent to which crime perpetrators experience and perceive social punishment (exclusion) from their social networks. Using a quota sampling strategy, we administered a cross-sectional questionnaire to perpetrators of femicide (N = 71), male–male homicide (N = 73), and other serious crimes (N = 64) across four prisons in Buenos Aires, Argentina. Other crime perpetrators served as a control to the two lethal crime groups. Perceived social capital scores were assigned based on responses to two scales adapted from the World Bank’s “Integrated Questionnaire for the Measurement of Social Capital.” Before committing murder, femicide and homicide perpetrators’ scores were not statistically different. Yet after the crime, femicide perpetrators retained significantly greater scores than homicide perpetrators. The perceived social capital scores of other crime perpetrators did not change after the commission of their crimes. As a secondary objective, we examined the individual and social contexts of femicide perpetrators. Most (85%) of the femicide perpetrators could name at least one other person in their social network whom they knew to be physically violent during disagreements with their partner, while 11% stated that “everyone” they knew used violence during disagreements. Although the penalty for committing femicide and homicide is ostensibly equivalent—a life sentence of 50 years—we found that the informal social punishment femicide perpetrators perceived is less severe than that experienced by homicide perpetrators. These data indicate a lack of social punishment for femicide, compared to other crimes, showing social legitimization of the crime. These findings support the development of community-level interventions to prevent femicide.